Analisis Penanganan Daerah Rawan Kecelakaan Ditinjau Dari Audit Keselamatan Jalan (Studi Kasus : Kec. Latambaga, Kab. Kolaka, Provinsi Sulawesi Tenggara) - Haerul Purnama; Bagus Eko Prasetyo; Zulfikar (Universitas Medan Area, 2023)
Latambaga District as part of the Kolaka Regency, in between 2019 to 2021 based on data from the Kolaka Police departement there were 69 accident cases, this is considered a quite significant increase considering that based on BPS data for 2015 the number of reported accidents in the entire Kolaka district was only 93 case. This study aimed to determining accident-prone locations using the Upper Control Limit (BKA) and Upper Control Limit (UCL) calculation methods in Latambaga sub-district and recommend treatment based on the relationship between the characteristics of the causes of accidents and the results of road safety audits. The results then showed that the characteristics of accidents in Latambaga sub districts were dominated by drivers with an age range of 16-25 years, namely 47.17%, based on the age characteristics of the victims, 43.54% were also dominated by the age range of 16-25 years. When accidents occur, 63% occur at night, at 18:00-24:00. Accident-prone locations in Latambaga sub-district, based on the results of blacksite & blackspot analysis, are in segment 1 (coordinates -4.037839,121.564658), segment 4 (coordinates -4.040031,121.564984) and segment 5 (coordinates: -4.055727,121.591074.). As for the priority treatment recommendations for accident-prone locations, for segment 1 it is recommended to complete intersection markings and signs. For segment 4, it is recommended to prioritize the installation of signs, street lights, safety thresholds, clarify the road median and make improvements to the road pavement. For segment 5 it is recommended to prioritize, improve road drainage to prevent puddle and improve road pavement conditions.